Microtubule Affinity-Regulating Kinase 2 (MARK2) Induces the Early Morphological Changes Seen in Pathological Cardiac Hypertrophy - Do, Michael (Université d'Ottawa / University of Ottawa, 2024)
Cardiac hypertrophy, a compensatory growth response to various physiological and pathological stimuli, involves intricate cytoskeletal changes within cardiomyocytes. However, the molecular mechanisms governing these cytoskeletal processes is not yet well defined. Microtubule affinity-regulating kinase 2 (MARK2) is of particular interest as it plays an important role in controlling microtubule dynamics and cell polarity to define cell shape. In this thesis, we aim to determine whether MARK2 is involved in initiating the morphological alterations that drive cardiac hypertrophy. Our image analysis reveals a significant increase in total MARK2 signal during pathological remodeling, particularly in the initial hours. However, no significant change occurs under physiological hypertrophy. Inhibiting MARK2 significantly impacts cell area and length-to-width ratio during pathological remodeling but has no effect under physiological conditions. Additionally, MARK2 inhibition results in decreased microtubule density and reduced Tau phosphorylation at Serine262 in pathological remodeling cardiomyocytes. Furthermore, our findings indicate an increased number of binucleated cardiomyocytes in pathological hypertrophy, with MARK2 inhibition influencing this parameter. Overall, our findings provide clarity in the role that MARK2 has in driving cytoskeleton alterations to shift cell morphology in pathological cardiac hypertrophy and a unique potential therapeutic in preventing the transition to fulminant heart failure.
Keywords: Pathological Cardiac Hypertrophy; MARK2